The Role of the Pesantren Rasyidiyah Khalidiyah Amuntai in the Formation of Islamic Traditions in South Kalimantan Society - Pahrurraji Pahrurraji; Ahmad Qusairi (Islamic Religious Education Master Program Universitas Islam Internasional Darullughah Wadda'wah, 2025)
Pesantren Rasyidiyah Khalidiyah in Amuntai plays a very significant role in the formation of Islamic traditions in South Kalimantan by integrating religious education and local culture. This study aims to analyze the impact of Islamic boarding schools on the development of Islamic traditions in the local community and their contribution to maintaining and developing Islamic values. The research method used is qualitative with a descriptive approach supported by interview, observation, and documentation techniques, involving the active participation of Islamic boarding school administrators, students, and the community around the boarding school. The results of the study show that through various religious activities held, such as the celebration of the Prophet Muhammad’s Birthday, Isra’ Wal Mi’raj, and the moon observation program (Hisab), this boarding school has not only succeeded in strengthening Islamic brotherhood among alumni and the community, but also increasing their spiritual awareness and concern for religious and social issues. The contribution of this study is an in-depth understanding of the role of Pesantren Rasyidiyah Khalidiyah in maintaining and developing relevant Islamic traditions, as well as providing valuable insights for the development of Islamic education and religious practices in various contexts.